Effect of organic solvents and ionic liquids on resolution of 2‐epoxyhexane by whole cells of Rhodotorula glutinis in a two‐liquid phase system. Issue 4 (4th July 2013) - Matsumoto, Michiaki; Sugimoto, Takashi; Ishiguro, Yudai; Yamaguchi, Hiroyuki; Kondo, Kazuo
Abstract BACKGROUND Enantiopure epoxides and diols have attracted much attention as important building blocks for the production of flavorings, agrochemicals and pharmaceutical products. Enantioselective hydrolysis reaction of rac‐epoxide in a biphasic system using whole cell catalysts is one of the promising methods to obtain enantiopure compounds. RESULTS The kinetic resolution of racemic 1, 2‐epoxyhexane was carried out using whole cell biocatalyst in a hydrophobic solvent/buffer biphasic system and the effect of organic solvents and ionic liquids on the initial reaction rate of (R)‐enantiomer, rR0 and enantiomeric ratio, E was examined. In the case of using hydrophobic hydrocarbons, rR0 increased with the hydrophobicity of hydrocarbon (log PO/W), and a linear correlation was observed between rR0 and log PO/W. On the other hand, there were no correlations between rR0 and log PO/W of ionic liquids. Moreover, effects on E were small in both solvents. However, the addition of 1‐heptanol to dodecane was very effective at increasing E value. The kinetic data correlated well with the reaction kinetic model, considering the distribution between two liquid phases and competitive product inhibition. CONCLUSION The high enantiomeric ratio of (R)‐diol (E>100) without significant decrease in the reactivity was accomplished by adding 1‐heptanol in minute amounts to dodecane. © 2013 Society of Chemical Industry